Hematoprotective and Nephroprotective Effects of Achillea millefolium Aqueous Extract in Diabetic Mice - Mohammad Mahdi Zangeneh* (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Achillea millefolium has been used in medicine as an anti-fungal, antibacterial and antioxidant agent. The present study was carried out to assess the hematoprotective and nephroprotective activities of Achillea millefolium aqueous extract (AMAE) in diabetic mice. Methods:  Seventy mice were used anddiabetes was experimentally induced by intraperitoneal injection of streptozotocin (STZ) (60 mg/kg) in 60 mice. The mice with serum glucose level>250 mg/dL were considered diabetic. After three days, they were divided randomly into 7 groups. Group 1 and 2 were non-diabetic and untreated diabetic controls, respectively. Group 3 received 30 mg/kg glibenclamide orally. Groups 4, 5, 6 and 7 were given 10, 30, 90 and 270 mg/kg of AMAE, respectively for 20 days orally. At 20th day, the mice were dissected, and the blood and kidney samples were collected for hematological and pathological parameters analysis. Results:  Daily treatment of diabetic mice with 10, 30, 90 and 270 mg/kg doses of AMAE at all doses especially 90 and 270 mg/kg significantly declined blood glucose, creatinine and urea levels and improved RBC (Red blood cell), platelet and WBC (White blood cell) parameters, compared to the untreated diabetic control. Also kidney of the treated diabetic mice with AMAE at all doses especially 270 mg/kg indicated significant improvement of the renal tissue compared to the untreated diabetic mice. Conclusion: The present research demonstrated the hypoglycemic properties of AMAE, offering to be suggested as an anti-diabetic supplement.